Do the Islamic Social Finance Institution Programs Realize the Sustainable Development Goals (SDGs)? Analysis of Dompet Dhuafa Program - Sahroni, Abdullah; Mardiah, Siti; Litriani, Erdah (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This research aims to analyze the role and contribution of Islamic social finance institutions in advancing the Sustainable Development Goals (SDGs) within the community of Palembang City, South Sumatra. The study is driven by the ongoing challenges of sustainable human development: particularly in the areas of education, health, and welfare for underprivileged communities, despite a recent decline in poverty and unemployment over the past three years. However, these issues still require further attention and strategic solutions. Dompet Dhuafa, as a prominent Islamic social finance institution, plays a significant role in enhancing human development outcomes in Palembang. This study employs a qualitative methodology using a phenomenological approach. Data were collected through field observations, in-depth interviews with selected informants, and document analysis. To ensure research credibility, triangulation and rich, thick descriptions were utilized. Data analysis was conducted qualitatively, supported by the Analytic Network Process (ANP) model. The impact of Dompet Dhuafa’s program on community development was measured based on targets established by Dompet Dhuafa. The findings indicate that Dompet Dhuafa contributes meaningfully by providing free healthcare services through the Layanan Kesehatan Cuma-Cuma (LKC), education scholarship for underprivileged students, and business capital asssitance to increase the income level. Funding for these programs is primarily sourced from productive waqf, supplemented by zakah and infaq contributions.